Magnetic resonance imaging compared to ultrasound as the preferred method for diagnosing intractable haematospermia. (6th May 2021) - Han, Hu; Lei, Hong‐en; Zhang, Xiao‐dong; Tian, Long
Abstract: We aimed to evaluate and compare the clinical diagnostic values of magnetic resonance imaging (MRI) and ultrasound in patients with intractable haematospermia. We performed a retrospective review of 23 patients with intractable haematospermia who were diagnosed with seminal vesicle haematocele and/or calculi by transurethral seminal vesiculoscopy (TSV). Patients' demographics, disease durations, operative times, and MRI and transrectal ultrasound (TRUS) results were recorded. McNemar's test was used to compare the positive diagnostic rates of MRI and TRUS. All patients had undergone preoperative seminal vesicle MRI and TRUS to identify the aetiology of the haematospermia. The average age and disease duration were 39.3 years and 24.1 months, respectively. The mean operative time was 81.1 min. The positive result rates for MRI and TRUS were 95.7% (22/23) and 39.1% (9/23), respectively. Compared with TRUS, MRI had a significantly higher preoperative positive diagnostic rate ( p  < 0.01). These results suggest that MRI should be considered as a method for diagnosing intractable haematospermia in patients when TRUS findings are negative or inconclusive.